PENGGUNAAN KAEDAH INKUIRI PENEMUAN TERHADAP MINAT PELAJAR DALAM EKSPERIMEN SAINS TAHUN 5 - Rubani, Siti Nur Kamariah; Norrahim, Norraliza; Hamzah, Norhasyimah; Ariffin, Arihasnida; Subramaniam, Tamil Selvan (Online Journal for TVET Practitioners, 2018)
Inquiry discovery based learning involves questioning, exploration of idea and observation during the teaching and learning process.The purpose of the study was to identify students’ interest in science experiments by using the inquiry discovery method. A total of 30 respondents was selected through purposive sampling method. The respondents consisted of studentsâ€™ from 5th grade at primary school in Malaysia. The data were analyzed using descriptive statistic. The finding showed that using inquiry discovery method in science experiment high mean level (mean = 4.47). Based on these findings, using inquiry discovery methodwill attract student interest in science experiment.